Application of W18O49 / graphene electrode material in nuclide uranium recovery
By using capacitive adsorption technology combined with activated carbon, the problem of low extraction efficiency of existing carbon-based materials on uranyl ions is solved, and efficient and stable uranyl ions recovery is achieved.
Patent Information
- Application Number
- CN202411670768.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing carbon-based materials have low efficiency in capturing uranyl ions through the electric double layer mechanism, making it difficult to achieve efficient nuclide uranium recovery.
The W18O49/graphene electrode material is used as the negative electrode of the capacitance deionization device, and the activated carbon material is used as the positive electrode to recover uranyl ions through capacitance adsorption.
It significantly improves the extraction capacity of uranyl ions, improves the stability and cost-effectiveness of electrode materials, and achieves efficient uranyl ions recovery.
Smart Images

Figure CN119503975A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials and nuclide recovery, and specifically relates to a W 18 O 49 / Application of graphene electrode materials in the recovery of radionuclide uranium. Background Art
[0002] With the rapid development of economy and the rapid growth of population, the use of non-renewable fossil energy such as coal and oil is increasing day by day, which has caused serious problems for society and environment, the greenhouse effect is becoming more and more serious, and energy shortage is becoming more and more obvious. As an indispensable nuclear fuel for the operation of nuclear power, the continuous supply of uranium is of great significance to the safe development of nuclear industry.
[0003] At present, domestic and foreign scholars have made certain progress in the technology of uranium extraction from seawater, but further efforts are needed to reach the industrial level. Over the past few decades, researchers have developed a variety of methods for uranium extraction from seawater, such as physical and chemical adsorption, solvent extraction, co-precipitation, biological treatment, ion exchange and membrane separation. However, the most widely used method for uranium extraction from seawater is physical and chemical adsorption. However, due to the limited surface area of the adsorption material, the uranium concentration in the ocean is low, the salinity is high and the environment is complex. At the same time, the active sites on the adsorption material used to adsorb uranyl ions are quickly saturated, and the ideal uranium extraction effect cannot be achieved. Therefore, the development of an efficient and selective uranium extraction technology is of great significance to the sustainable development of nuclear energy.
[0004] Capacitive deionization technology is a new technology based on the theory of capacitive deionization, which has the characteristics of low energy consumption, low cost and environmental friendliness. Capacitive deionization technology has broad application prospects in domestic sewage treatment, tap water purification, industrial wastewater treatment and other aspects. Commonly used capacitive deionization forms: double-layer capacitors. A certain voltage is applied between the two electrodes. When the solution flows between the two electrodes, under the action of the electric field, the ions will move toward the electrode with opposite electrical properties and eventually be adsorbed on the electrode. Therefore, the concentration of the solution flowing out of the deionization device will decrease, and the deionization effect will be achieved. When the ions moving into the pores of the electrode material reach saturation, the two electrodes are reversely connected, and the ions in the pores are released again, so that the electrode can be regenerated. Commonly used carbon materials have large specific surface area, high conductivity, good electrochemical stability and rich pore structure. However, the existing carbon-based materials capture charged ions through the double-layer mechanism, and the extraction efficiency of uranyl ions is low. The development of an efficient and stable electrode material for application in the recovery of radionuclide uranium has broad prospects. Summary of the invention
[0005] In view of the shortcomings and deficiencies of the above prior art, the object of the present invention is to provide a 18 O49 / Application of graphene electrode materials in the recovery of radionuclide uranium.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A W 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, the application method is: W 18 O 49 / Graphene electrode material is used as the negative electrode of the capacitive deionization device, and activated carbon material is used as the positive electrode, and then uranyl ions are recovered by capacitive adsorption.
[0008] Furthermore, the voltage adsorbed by the capacitor is 0.1-5V.
[0009] Furthermore, the W 18 O 49 / The graphene electrode material is prepared by the following method:
[0010] (1) dispersing ammonium tungstate and graphene in a tris(hydroxymethyl)aminomethane solution and heating and stirring to react to obtain a mixed solution;
[0011] (2) dispersing dopamine hydrochloride, ethanol and ammonia water in the mixed solution of step (1) in sequence and stirring to react, and washing and drying the product to obtain a precursor;
[0012] (3) The precursor obtained in step (2) is carbonized in an inert atmosphere at a temperature of 600 to 900° C. to obtain W 18 O 49 / Graphene electrode materials.
[0013] Furthermore, the mass concentration of the tris(hydroxymethyl)aminomethane solution in step (1) is 0.1-5 mg / mL.
[0014] Furthermore, the amount of ammonium tungstate added in step (1) is 0.1 to 4 times the mass of dopamine hydrochloride in step (2).
[0015] Furthermore, the amount of graphene added in step (1) is 0.1 to 1 times the mass of dopamine hydrochloride in step (2).
[0016] Furthermore, the heating and stirring reaction in step (1) refers to stirring the reaction at 30 to 80° C. for 0.1 to 6 hours.
[0017] Furthermore, the amount of ethanol added in step (2) is 0.1 to 200 times the mass of the ammonium tungstate in step (1). The addition of ethanol in the preparation process of the present invention is beneficial to the dispersion of ammonium tungstate and graphene.
[0018] Furthermore, the amount of ammonia water added in step (2) is 0.1 to 5 times the mass of the ammonium tungstate in step (1). The addition of ammonia water in the preparation process of the present invention is beneficial to the decomposition of ammonium tungstate.
[0019] Furthermore, the stirring reaction in step (2) refers to stirring the reaction at room temperature for 6 to 24 hours; the washing refers to washing with deionized water, and the drying refers to drying at a temperature of 100 to 140°C.
[0020] Furthermore, the inert atmosphere in step (3) refers to a nitrogen atmosphere or an argon atmosphere; and the carbonization treatment time is 5 to 500 minutes.
[0021] The principle of the present invention is: through the pseudocapacitor material W 18 O 49 The introduction of W can significantly improve the deionization capacity of capacitors. Unlike porous carbon electrodes that store ions in double electrical layers, pseudocapacitors can store ions through electrochemical effects such as ion intercalation and conversion. 18 O 49 With high specific capacitance and adjustable interlayer spacing, it can provide a larger ion storage space for ion transport. At the same time, a larger interlayer spacing can also effectively increase the adsorption capacity of ions. In addition, W 18 O 49 There is W in the lattice 4 + , W 5+ and W 6+ Multiple valence states result in too many electrons and lattice distortion between the interlayers. When the third phase cation is inserted, a large number of free electrons will gather on the lattice surface, which is conducive to the adsorption of cations. However, due to the single component W 18 O 49 The conductivity of W is low and the specific surface area is small, so the efficiency of its capacitive adsorption and recovery of uranyl ions is low. 18 O 49 / Graphene is a kind of outer layer composed of graphene flake structure and inner layer composed of W 18 O 49 The pseudocapacitive electrode with a spherical flower-like layered structure can enhance the extraction ability of uranyl ions in complex wastewater through the pseudocapacitive effect.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention adopts W 18 O 49 / Graphene electrode materials replace conventional carbon materials for capacitive adsorption and recovery of uranyl ions, which can significantly improve the extraction capacity of uranyl ions.
[0024] (2) The present invention18 O 49 / The synthesis process of graphene electrode materials is simple, there is no stacking problem, the stability is good, and it is not easily soluble in acidic or alkaline solutions. Its performance in capacitive adsorption recovery of uranyl ions is stable and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 W prepared in Example 1 18 O 49 / Scanning electron microscope image of graphene electrode material;
[0026] Figure 2 W prepared in Example 1 18 O 49 / TEM image of graphene electrode material;
[0027] Figure 3 W prepared in Example 1 18 O 49 / XPS and element content distribution of graphene electrode materials;
[0028] Figure 4 W prepared in Example 1 18 O 49 / graphene electrode material and activated carbon material (AC) of comparative example 1, W of comparative example 2 18 O 49 Comparison of recovery efficiency of electrode materials for uranyl ions of different concentrations.
[0029] Figure 5 W prepared in Example 1 18 O 49 / graphene electrode material and activated carbon material (AC) of comparative example 1, W of comparative example 2 18 O 49 Comparison of the selective recovery efficiency of electrode materials for 10ppm uranyl ions.
[0030] Figure 6 W prepared in Example 1 18 O 49 / Graphene electrode material recovery efficiency of uranyl ions at different cycle numbers. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0032] Example 1
[0033] 1. W 18 O 49 / Preparation of graphene electrode materials:
[0034] (1) 1.2 g of ammonium tungstate powder and 0.1 g of graphene were weighed and dispersed in 200 mL of 1 mg / mL tris(hydroxymethyl)aminomethane solution, and reacted under magnetic stirring at 80° C. for 30 minutes to obtain a mixed solution.
[0035] (2) Weigh 0.4 g of dopamine hydrochloride and disperse it in the above mixed solution, stir it under magnetic stirring at room temperature for 2 hours, then add 160 mL of ethanol and stir it for 2 hours, and finally add 1.2 mL of ammonia water and stir it for 2 hours. The product after the reaction is washed with deionized water, filtered, and dried at 120° C. to obtain a precursor.
[0036] (3) The obtained precursor sample was placed in a tube furnace and subjected to heating carbonization treatment under an Ar inert atmosphere. The heating carbonization treatment temperature was 750° C. and the time was 180 minutes to obtain W 18 O 49 / Graphene electrode materials.
[0037] This embodiment W 18 O 49 The scanning electron microscope and transmission electron microscope images of the graphene electrode material are shown in Figure 2. Figure 1 and Figure 2 As shown, W 18 O 49 / Element distribution diagram of graphene electrode materials Figure 3 As shown. It can be seen that the W obtained by the present invention 18 O 49 / The outer layer of the graphene electrode material is composed of a graphene sheet structure, and the inner layer is composed of W 18 O 49 It is composed of a spherical flower-like layered structure, in which the mass ratio of tungsten, oxygen, nitrogen and carbon is 3.77:14.38:2.36:79.49.
[0038] 2. W obtained in this embodiment 18 O 49 / Application of graphene electrode materials in uranyl ion recovery. The specific application methods are as follows:
[0039] The obtained W 18 O 49 / Graphene electrode material is used as the negative electrode of the capacitive deionization device, and activated carbon is used as the positive electrode of the capacitive deionization device. Under the action of 1.2V voltage, the capacitive adsorption of uranyl ions in uranyl nitrate solutions of different concentrations (10ppm, 30ppm, 50ppm, 70ppm, 90ppm) is carried out. The capacitive adsorption solution is tested by ICP-OES to calculate the uranyl ion recovery rate. The test results are as follows: Figure 4 As shown. Figure 4 As a result, it can be seen that the W 18 O 49 / The graphene electrode material has a recovery efficiency of 96.93% for uranyl ions with a solubility of 10ppm, 96.91% for uranyl ions with a solubility of 30ppm, 95.69% for uranyl ions with a solubility of 50ppm, 95.54% for uranyl ions with a solubility of 70ppm, and 94.34% for uranyl ions with a solubility of 90ppm.
[0040] The obtained W 18 O 49 / Graphene electrode material is used as the negative electrode of the capacitor deionization device, and activated carbon is used as the positive electrode of the capacitor deionization device. Under the action of 1.2V voltage, the capacitor adsorbs uranyl ions in a mixed solution of 10ppm uranyl nitrate and 100ppm sodium chloride. The solution adsorbed by the capacitor is tested by ICP-OES to calculate the recovery rate of uranyl ions. The test results are as follows Figure 5 As shown. Figure 5 As a result, it can be seen that the W obtained in this embodiment 18 O 49 The selective recovery efficiency of uranyl ions of the graphene electrode material is 95.87%.
[0041] At the same time, the obtained W 18 O 49 / Graphene electrode material is used as the negative electrode of the capacitor deionization device, and activated carbon is used as the positive electrode of the capacitor deionization device. The capacitor adsorbs uranyl ions in a mixed solution of 10ppm uranyl nitrate and 100ppm sodium chloride under a voltage of 1.2V. The solution adsorbed by the capacitor at different cycle times was tested by ICP-OES to calculate the recovery rate of uranyl ions. The test results are shown in Figure 6 As shown. Figure 6 As a result, it can be seen that the W obtained in this embodiment 18 O 49 / Graphene electrode materials have stable selective recovery efficiency for uranyl ions.
[0042] Example 2
[0043] 1. W 18 O 49 / Preparation of graphene electrode materials:
[0044] (1) 1.2 g of ammonium tungstate powder and 0.4 g of graphene were weighed and dispersed in 200 mL of 1 mg / mL tris(hydroxymethyl)aminomethane solution, and reacted under magnetic stirring at 80° C. for 30 minutes to obtain a mixed solution.
[0045] (2) Weigh 0.4 g of dopamine hydrochloride and disperse it in the above mixed solution, stir it under magnetic stirring at room temperature for 2 hours, then add 160 mL of ethanol and stir it for 2 hours, and finally add 1.2 mL of ammonia water and stir it for 2 hours. The product after the reaction is washed with deionized water, filtered, and dried at 140° C. to obtain a precursor.
[0046] (3) The obtained precursor sample was placed in a tube furnace and subjected to heating carbonization treatment under an Ar inert atmosphere. The heating carbonization treatment temperature was 900° C. and the time was 30 minutes to obtain W 18 O 49 / Graphene electrode materials.
[0047] 2. W obtained in this embodiment 18 O 49 / Application of graphene electrode material in uranyl ion recovery, the specific application method is the same as Example 1.
[0048] The W obtained in this embodiment 18 O 49 The recovery efficiency of the graphene electrode material for uranyl ions with a solubility of 10 ppm is 94.23%, the recovery efficiency of uranyl ions with a solubility of 30 ppm is 94.19%, the recovery efficiency of uranyl ions with a solubility of 50 ppm is 94.11%, the recovery efficiency of uranyl ions with a solubility of 70 ppm is 94.01%, and the recovery efficiency of uranyl ions with a solubility of 90 ppm is 93.87%.
[0049] Example 3
[0050] 1. W 18 O 49 / Preparation of graphene electrode materials:
[0051] (1) 1.2 g of ammonium tungstate powder and 0.05 g of graphene were weighed and dispersed in 200 mL of 1 mg / mL tris(hydroxymethyl)aminomethane solution, and reacted under magnetic stirring at 50° C. for 30 minutes to obtain a mixed solution.
[0052] (2) Weigh 0.4 g of dopamine hydrochloride and disperse it in the above mixed solution, stir it under magnetic stirring at room temperature for 2 hours, then add 160 mL of ethanol and stir it for 2 hours, and finally add 1.2 mL of ammonia water and stir it for 2 hours. The product after the reaction is washed with deionized water, filtered, and dried at 100° C. to obtain a precursor.
[0053] (3) The obtained precursor sample was placed in a tube furnace and subjected to heating carbonization treatment in an Ar inert atmosphere at a temperature of 600° C. for 480 minutes to obtain W 18 O 49 / Graphene electrode materials.
[0054] 2. W obtained in this embodiment 18 O 49 / Application of graphene electrode material in uranyl ion recovery, the specific application method is the same as Example 1.
[0055] The W obtained in this embodiment 18 O 49 / The graphene electrode material has a recovery efficiency of 93.67% for uranyl ions with a solubility of 10ppm, 93.45% for uranyl ions with a solubility of 30ppm, 93.32% for uranyl ions with a solubility of 50ppm, 93.12% for uranyl ions with a solubility of 70ppm, and 92.59% for uranyl ions with a solubility of 90ppm.
[0056] Comparative Example 1
[0057] In this comparative example, activated carbon material (AC) was used to replace W in Example 1. 18 O 49 / Graphene electrode materials.
[0058] The application of the activated carbon electrode material of this comparative example in the recovery of uranyl ions is similar to that of Example 1.
[0059] The recovery test results of uranyl ions with different concentrations adsorbed by capacitance under 1.2V voltage are shown in the figure below. Figure 4 shown.
[0060] Depend on Figure 4 The results show that the recovery efficiency of the conventional activated carbon electrode material for uranyl ions with a solubility of 10 ppm is 65.54%, the recovery efficiency of uranyl ions with a solubility of 30 ppm is 65.43%, the recovery efficiency of uranyl ions with a solubility of 50 ppm is 63.73%, the recovery efficiency of uranyl ions with a solubility of 70 ppm is 61.83%, and the recovery efficiency of uranyl ions with a solubility of 90 ppm is 60.58%.
[0061] Activated carbon was used as the positive and negative electrodes of the capacitive deionization device. The uranyl ions in the mixed solution of 10ppm uranyl nitrate and 100ppm sodium chloride were capacitively adsorbed under a voltage of 1.2V. The capacitively adsorbed solution was tested by ICP-OES to calculate the uranyl ion recovery rate. The test results are as follows: Figure 5 As shown. Figure 5 The results show that the recovery efficiency of the activated carbon electrode material of this comparative example for uranyl ions is 65.52%, and the recovery efficiency for sodium ions is 42.54%.
[0062] By comparing the results of this comparative example with those of Example 1, it can be seen that the present invention W18 O 49 Compared with activated carbon materials, the selective recovery efficiency of uranyl ions is significantly improved by graphene electrode materials.
[0063] Comparative Example 2
[0064] This comparative example uses W 18 O 49 The electrode material replaces W in Example 1 18 O 49 / Graphene electrode materials.
[0065] 1. W 18 O 49 Preparation of electrode materials:
[0066] (1) 1.2 g of ammonium tungstate powder was weighed and dispersed in 200 mL of 1 mg / mL tris(hydroxymethyl)aminomethane solution, and the mixture was reacted at 80° C. with magnetic stirring for 30 minutes to obtain a mixed solution.
[0067] (2) Weigh 0.4 g of dopamine hydrochloride and disperse it in the above mixed solution, stir it under magnetic stirring at room temperature for 2 hours, then add 160 mL of ethanol and stir it for 2 hours, and finally add 1.2 mL of ammonia water and stir it for 2 hours. The product after the reaction is washed with deionized water, filtered, and dried at 120° C. to obtain a precursor.
[0068] (3) The obtained precursor sample was placed in a tube furnace and subjected to heating carbonization treatment under an Ar inert atmosphere. The heating carbonization treatment temperature was 750° C. and the time was 180 minutes to obtain W 18 O 49 Electrode material.
[0069] W of this comparative example 18 O 49 The application of the electrode material in the recovery of uranyl ions, and the specific application method are the same as in Example 1.
[0070] The recovery test results of uranyl ions with different concentrations adsorbed by capacitance under 1.2V voltage are shown in the figure below. Figure 4 shown.
[0071] Depend on Figure 4 The results show that this comparative example adopts W 18 O 49 The electrode material has a recovery efficiency of 86.78% for uranyl ions with a solubility of 10 ppm, 86.49% for uranyl ions with a solubility of 30 ppm, 84.28% for uranyl ions with a solubility of 50 ppm, 82.26% for uranyl ions with a solubility of 70 ppm, and 80.38% for uranyl ions with a solubility of 90 ppm.
[0072] W 18 O 49 It is used as the positive and negative electrodes of the capacitive deionization device. Under the action of 1.2V voltage, the capacitor adsorbs uranyl ions in a mixed solution of 10ppm uranyl nitrate and 100ppm sodium chloride. The solution adsorbed by the capacitor is tested by ICP-OES to calculate the recovery rate of uranyl ions. The test results are as follows: Figure 5 As shown. Figure 5 As a result, it can be seen that W 18 O 49 The electrode material has a recovery efficiency of 86.75% for uranyl ions and 41.43% for sodium ions.
[0073] By comparing the results of this comparative example with those of Example 1, it can be seen that the present invention uses graphene to 18 O 49 Doping and compounding of electrode materials can further improve the efficiency of capacitor adsorption and recovery of uranyl ions.
[0074] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A W 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that: The application method is: W 18 O 49 / Graphene electrode material is used as the negative electrode of the capacitive deionization device, and activated carbon material is used as the positive electrode, and then uranyl ions are recovered by capacitive adsorption.
2. A W according to claim 1 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that: The voltage adsorbed by the capacitor is 0.1-5V.
3. A W according to claim 1 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that, The W 18 O 49 / The graphene electrode material is prepared by the following method: (1) dispersing ammonium tungstate and graphene in a tris(hydroxymethyl)aminomethane solution and heating and stirring to react to obtain a mixed solution; (2) dispersing dopamine hydrochloride, ethanol and ammonia water in the mixed solution of step (1) in sequence and stirring to react, and washing and drying the product to obtain a precursor; (3) The precursor obtained in step (2) is carbonized in an inert atmosphere at a temperature of 600 to 900° C. to obtain W 18 O 49 / Graphene electrode materials.
4. A W according to claim 3 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that, The mass concentration of the tris(hydroxymethyl)aminomethane solution in step (1) is 0.1-5 mg / mL.
5. A W according to claim 3 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that: The amount of ammonium tungstate added in step (1) is 0.1 to 4 times the mass of dopamine hydrochloride in step (2); and the amount of graphene added is 0.1 to 1 times the mass of dopamine hydrochloride in step (2).
6. A W according to claim 3 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that, The heating and stirring reaction in step (1) refers to stirring the reaction at 30 to 80° C. for 0.1 to 6 hours.
7. A W according to claim 3 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that, The amount of ethanol added in step (2) is 0.1 to 200 times the mass of ammonium tungstate in step (1).
8. A W according to claim 3 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that: The amount of ammonia water added in step (2) is 0.1 to 5 times the mass of ammonium tungstate in step (1).
9. A W according to claim 3 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that, The stirring reaction in step (2) refers to stirring the reaction at room temperature for 6 to 24 hours; the washing refers to washing with deionized water, and the drying refers to drying at a temperature of 100 to 140°C.
10. A W according to claim 3 18 O 49 / Application of graphene electrode material in the recovery of nuclide uranium, characterized in that: The inert atmosphere in step (3) refers to a nitrogen atmosphere or an argon atmosphere; the carbonization treatment time is 5 to 500 minutes.
Citation Information
Patent Citations
Preparation method of biomass source N / P co-doped carbon aerogel / cross-linked chitosan composite membrane electrode
CN111875006A
Flowing electrode, application and regeneration method thereof, and method for enriching uranium in uranium-containing water body by using flowing electrode capacitive deionization device
CN117383666A
Production of electrode and electrode
JP1999061398A